Protein efficiency of hydrolyzed feather meal substitution in sheep ration - Wisri Puastuti; I Wayan Mathius (Indonesian Center for Animal Research and Development (ICARD), 2007)
The use of protein ration in ruminant is affected by the characteristic of protein. The present study was carried out to evaluate the efficiency of protein of hydrolyzed feather meal (HBA) in ration for growing sheep. Twenty-five young rams of 7-8 months old with an average body weight of 21.16 ± 2.47 kg were used in this study. This study was conducted for 12 weeks based on randomized block design (5x5). The control treatment (R0) contained 72% of total digestible nutrient (TDN) and 15% total crude protein (CP), whereas R1-R4 treatments were fed on improved ration containing 75% TDN and 18% CP where HBA was used to substitute feed protein and as by pass protein source. The HBA substitution was carried out in 5 levels, namely: R0 = grass + concentrate with 0% HBA; R1 = grass + concentrate with 1.1% HBA; R2 = grass + concentrate with 2.2% HBA; R3 = grass + concentrate with 4.4% HBA and R4 = grass + concentrate with 8.5% The result showed that an increase of CP in ration and HBA substitution might increase CP consumption (P<0.01) but CP digestibility were not affected. HBA substitution increased (P<0.01) the average daily gain (ADG) from 90.91 g/head (R0) to 125.33 g/head (R1-R4) or increased 37.86%, but it did not affect the efficiency of protein ration. The respons of HBA substitution levels in ration (x) to ADG followed the equation, ADG = 1.641x2 + 15.778x + 99.372 (r2 = 72.37%). It is concluded that 8.5% HBA substitution in ration can substitute 100% soybean meal, and 2.2% HBA substitution in ration gives the best efficiency to support daily gain. Key Words: Protein, Feather Meal, Substitution, Sheep